Ébola in TChM: Diagnosis, Principles of Treatment and Economical Analysis - García Sánchez, M. Dolores (My University, 2015)
In this research we go more deeply into EVD, studying the Etiology and realizing a Differentiation of Syndromes according to the systems: Wen Bing, San Jiao and Han Shan Lun. Later, a Treatment for Prevention, Symptomatic/Acute, and Remission phases is proposed. Finally, we study the economic effects of the epidemic in the most affected countries by stressing the importance of preventive health care and international aid, looking at the usefulness of Medical Matter for its low cost especially in the affected societies (that probably they will return to be).
Investigación sobre etiología y tratamiento con MTC del ébola, especial referencia al entorno económico
Keywords: Medicina china; EVD; Wen Bing; Epidemic; African economy; Ébola